Cash Waqf Accountability and Digital Technology in West Sumatera: A Case Study - Gusrianti, Gusrianti; Syafitri, Rahmadya (IAIN Kudus, 2025)
This study investigates the utilization of digital technology in promoting accountability for cash waqf in West Sumatra. Employing a qualitative case study approach, Nazhir M was selected as the research subject due to its diverse waqf programmes, strong management, wide range of donors, multi-location operations, and foundation on key waqf principles. Data were gathered through semi-structured interviews and document analysis, with thematic analysis applied during data evaluation. The findings indicate that Nazhir M has adopted digital technology to enhance accountability, albeit at a basic level, primarily throught its official website and social media platforms. While Nazhir M possesses skilled personnel capable of utilising waqf accounting applications such as SAMAWI, manual financial reporting remains prevalent due to regulatory constraints. This research highlights the significant influence of regulatory authorities in shaping accountability practices among cash waqf nazhir through digital technology implementation. Furthermore, it offers a meaningful contribution to existing scholarship by delivering a comprehensive examination of digital technology adoption, highlighting the importance of nazhir intent and expertise, as well as the pivotal role of regulatory bodies.